Síntese assistida por micro-ondas de tiossemicarbazonas derivadas da isatina com potencial atividade biológica - Silva, Thaysa Suellen Mendonça da (2018)
Isatin and its derivatives have been presented in the literature with a broad pharmacological profile. Their Schiff bases, for example, present anticancer, antimicrobial and antiviral activities, so they are extensively explored in the literature. Based on this, this work was carried out with the objective of synthesizing and investigating the biological activity of some thiosemicarbazones derived from isatin. Of the ten thiosemicarbazones synthesized, six are unpublished in the literature and were obtained through the cheiosselective condensation reaction of thiosemicarbazide (9) with the ketonic portion of intermediates derived from isatin. These intermediates were obtained via nitration, chlorination and N-alkylation of the isatin. Six of these derivatives are homodimeric and were obtained in good yields (64-94%). The use of microwave irradiation (100 ° C) considerably reduced the reaction time of thiosemicarbazones compared to the methods described in the literature that make use of reflux and catalysis. The yields obtained were also quite satisfactory and ranged from 70 to 84%. Preliminary evaluation of the activity of thiosemicarbazones obtained and intermediates derived from isatin against strains of yeast bacteria and fungi was carried out. It was observed that thiosemicarbazones did not present antimicrobial biological activity, however, isatin and its nitrated and alil derivatives presented antimicrobial action (MIC = 128 to 512 μg.mL-1). The structural characterization of the compounds was performed by infrared (IR) spectroscopy and 1H and 13C NMR.